Elevating Retail Experience: The Role of IoT in Smart Shopping Carts - Kumar Yegireddy, Narendra; N V S S Kumar, M; Santosh Kumar, Gottapu (International Journal of Psychosocial Rehabilitation, 2020)
The retail assiduity is witnessing a rapid-fire metamorphosis, primarily driven by the wide relinquishment of Internet of Effects (IoT) results. These inventions aim to enhance client fidelity and produce a further flawless shopping experience. This exploration proposes a robust and effective result to streamline the shopping process and elevate customer satisfaction. By using smart detectors and RFID technologies, retail stores can offer shoppers a more individualized and effective shopping trip. The integration of RFID markers, attached to each product, enables automatic scanning by RFID compendiums. This process displays detailed product information on digital defences bedded within shopping wagons. This real-time access to product details empowers guests to make informed opinions, perfecting their overall shopping experience. Likewise, the perpetration of smart detectors strategically placed throughout the store assists new guests, barring the need for homemade wain navigation. The combination of RFID and smart detector technologies ensures a smoother and further instructional shopping experience. At the conclusion of their shopping trip, the system seamlessly connects to a central station using RF transceiver technology for force updates and billing. It presents a comprehensive summary of bought particulars and the total wain quantum, easing an accessible payment process through QR law scanning. By simplifying the checkout process, guests witness reduced delay times and increased effectiveness. The counteraccusations of this exploration extend beyond the retail sector, as the proposed technologies have the eventuality to transfigure colourful diligence. By enhancing the shopping experience through IoT results, this approach not only fosters client satisfaction and fidelity but also sets the stage for a further connected and effective future across different disciplines, eventually perfecting the overall quality of life for consumers. Once customers have completed their shopping, the system seamlessly connects to a central server via RF transmitter technology. This connection serves multiple purposes, including inventory updates and facilitating the billing process. It provides customers with a comprehensive breakdown of their purchases and the total cart amount, and the payment process becomes a breeze as customers can conveniently settle their bills by scanning a QR code. The integration of these technologies not only expedites the checkout process but also contributes to a more efficient and hassle-free shopping experience. The implications of this research transcend the realm of retail, extending its potential benefits to other industries. By enhancing the shopping experience through IoT solutions, this approach holds the promise of not only increasing customer satisfaction and loyalty but also setting the stage for a more interconnected, efficient, and enriching future across diverse domains. Ultimately, these innovations aim to improve the overall quality of life for consumers, creating a more harmonious and user-friendly world.